An Investigation into In-Store Customer Experience and Its Influence on Purchasing Intention of Male Chinese Luxury Fashion Consumers - Ma, Chaoyi (2019)
China has become the most attractive luxury fashion product market, in which male consumers were major segment in luxury fashion products consumption, and luxury fashion products consumption mainly took place in retail stores. Meanwhile, experience marketing has dynamically developed. This encouraged researchers to focus on how to understand, improve and utilize customer experience in marketing activities, especially marketing of physical retail stores. Although it has captured the attention of scholars and practitioners, there still were not many related studies.